2020
DOI: 10.1101/2020.01.27.921254
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A unified computational model for cortical post-synaptic plasticity

Abstract: Cortical synapses possess a machinery of signalling pathways that leads to various modes of post-synaptic plasticity. Such pathways have been examined to a great detail separately in many types of experimental studies. However, a unified picture on how multiple biochemical pathways collectively shape the observed synaptic plasticity in the neocortex is missing. Here, we built a biochemically detailed model of post-synaptic plasticity that includes the major signalling cascades, namely, CaMKII, PKA, and PKC pat… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(29 citation statements)
references
References 90 publications
2
27
0
Order By: Relevance
“…Third, like most biophysical models, ours contained many parameters (Methods). Although we set these to physiologically plausible values and then tuned to match the plasticity data, other combinations of parameters may fit the data equally well (Marder and Taylor, 2011;Mäki-Marttunen et al, 2020) due to the ubiquitous phenomenon of redundancy in biochemical and neural systems (Gutenkunst et al, 2007;Marder, 2011). Indeed synapses are quite heterogeneous in receptor and ion channel counts (Takumi et al, 1999;Sabatini and Svoboda, 2000;Racca et al, 2000;Nimchinsky et al, 2004), protein abundances (Shepherd and Harris, 1998;Sugiyama et al, 2005), and spine morphologies (Harris and Stevens, 1989;Bartol et al, 2015), even within the subpopulation of CA1 pyramidal neuron synapses that we modelled here.…”
Section: Discussionmentioning
confidence: 99%
“…Third, like most biophysical models, ours contained many parameters (Methods). Although we set these to physiologically plausible values and then tuned to match the plasticity data, other combinations of parameters may fit the data equally well (Marder and Taylor, 2011;Mäki-Marttunen et al, 2020) due to the ubiquitous phenomenon of redundancy in biochemical and neural systems (Gutenkunst et al, 2007;Marder, 2011). Indeed synapses are quite heterogeneous in receptor and ion channel counts (Takumi et al, 1999;Sabatini and Svoboda, 2000;Racca et al, 2000;Nimchinsky et al, 2004), protein abundances (Shepherd and Harris, 1998;Sugiyama et al, 2005), and spine morphologies (Harris and Stevens, 1989;Bartol et al, 2015), even within the subpopulation of CA1 pyramidal neuron synapses that we modelled here.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple chemical pathways depend on this elevation of postsynaptic calcium (Bhalla & Iyengar, 1999;Mäki-Marttunen et al, 2020). For calcium to be elevated at the synapse, it may arise from NMDAR-mediated currents, local release from calcium stores or VGCCs.…”
Section: Burst-dependent Synaptic Plasticitymentioning
confidence: 99%
“…We used the CommonMind gene-expression datasets from post-mortem brains of SCZ patients and healthy controls (HCs) [Hoffman et al, 2019] that provide the information on whether the expression of genes, particularly those associated with risk single-nucleotide polymorphisms (SNPs), are up-or down-regulated or unaffected in SCZ. We applied a computational model [Mäki-Marttunen et al, 2020] to the patients' brain gene expression data and investigated the effects of gene variants on the pathways that lead to long-term potentiation (LTP) and depression (LTD).…”
Section: Introductionmentioning
confidence: 99%
“…Using the model of [Mäki-Marttunen et al, 2020] we explored the impact that the altered expression profile of plasticityregulating genes, as measured in prefrontal cortices (PFC) and anterior cingulate cortices (ACC) of SCZ patients, have on several forms of synaptic plasticity. We showed that both the conventional forms of plasticity and the plasticity induced by the VEP protocol are significantly impaired by the alterations of protein levels suggested by post-mortem expression data and that these alterations are driven by impaired PKA-pathway-mediated synaptic potentiation.…”
Section: Introductionmentioning
confidence: 99%